Amphetamine Derivatives as Potent Central Nervous System Multitarget SERT/NET/H3 Agents: Synthesis and Biological Evaluation - Quxiang Li; Lili Ren; Dongli Wang; Junyong Luo; Changda Xu; Jian Feng; Yufan Qiu; Xiangqing Xu; Guoguang Chen (Molecules)
In this research, a variety of novel amphetamine derivatives were synthesized and assessed for their potential as multifaceted antidepressant agents. Among these compounds, compound 11b demonstrated potent inhibitory effects on both serotonin and noradrenaline transporters (SERT/NET) and high affinity for histamine H3 receptor (H3R), and displayed low affinity for off-target receptors (H1, α1) and hERG channels, which can reduce the prolongation of the QT interval. Molecular docking studies offered a rational binding model of compound 11b when it forms a complex with SERT, NET, and the histamine H3 receptor. In vivo behavioral studies, compound 11b dose-dependently reduced the immobility duration in the mouse FST and TST assays without a stimulatory effect on the locomotor activity. Furthermore, compound 11b had a favorable pharmacokinetic profile in rats. Thus, compound 11b has the potential to develop a novel class of drugs for the treatment of depression.